2019
DOI: 10.1097/pec.0000000000001084
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the Toxicity and Dose-Effect Profile of Tramadol Ingestions in Children

Abstract: Seizure and respiratory depression are uncommon in pediatric tramadol ingestions. Given the small number of patients with dose data and lack of laboratory confirmation of dose, more studies are needed to determine the minimum dose at which medical management is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…To evaluate tramadol toxicity in children, a retrospective assessment of 7334 cases, of children aged <6 years and tramadol acute ingestion only, was performed (Stassinos et al., ). Only one death was observed, while in most of the children, no effects were observed (84.8%); minor effects were observed in 12.6% of the sample, moderate in 2.2% and major in 0.4% only (Stassinos et al., ).…”
Section: Clinical Applications and Efficacymentioning
confidence: 99%
“…To evaluate tramadol toxicity in children, a retrospective assessment of 7334 cases, of children aged <6 years and tramadol acute ingestion only, was performed (Stassinos et al., ). Only one death was observed, while in most of the children, no effects were observed (84.8%); minor effects were observed in 12.6% of the sample, moderate in 2.2% and major in 0.4% only (Stassinos et al., ).…”
Section: Clinical Applications and Efficacymentioning
confidence: 99%
“…By contrast, another self-controlled study concluded to the efficacy and safety of 0.05 mg naloxone administered IV every 3-5 min after initial resuscitation to manage tramadol-intoxicated patients with postseizure complaints [15]. In addition, tramadol-poisoned children are at risk of apnea and seizures highlighting the necessity to define an efficient and safe antidote to reverse central nervous system (CNS) toxicity, considering the European advice for the treatment of moderate pain in children suggesting limited codeine use and rather tramadol prescription [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…In Europe, tramadol is approved and licensed for use in children over 1–3 years of age, depending on the countries, for moderate to severe nociceptive pain management. In the United States, tramadol is only approved for children older than 17 years of age, but appears to be regularly used nevertheless ( Friedrichsdorf et al, 2015 ; Stassinos et al, 2017 ). Despite a lack of precise data, it is recognized that its prescription has increased in children after codeine was contraindicated ( Mahic et al, 2015 ).…”
Section: History Of Tramadolmentioning
confidence: 99%
“…The most common ADR, in both adults and children, after single and multiple doses are dizziness, nausea, confusion, drowsiness, tiredness, vomiting, constipation, headache, and dry mouth ( Gibson, 1996 ; Rose et al, 2003 ; Moyao-Garcia et al, 2009 ). Respiratory depression, impaired consciousness, sedation, and seizure are rare, often related to tramadol overdose ( Hassanian-Moghaddam et al, 2015 ; Tsutaoka et al, 2015 ; Stassinos et al, 2017 ). Due to its monoaminergic effects, tramadol increases the concentration of serotonin in the synaptic cleft and has been associated with serotonin syndrome in adults, in particular when combined with serotoninergic drugs ( Beakley et al, 2015 ; Ansari and Kouti, 2016 ).…”
Section: Pharmacodynamicsmentioning
confidence: 99%